Lingkup Kerja Pelayanan Masyarakat Pada Kantor Desa Mekarsari Tambun Selatan - Azahra, Fallya; Thamrin, Djuni; Siahaan, Matdio; Renwarin, Joseph Martinio Jocrien; H, Hadita (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The aim of this research is to find out the scope of work and what factors support the services of the Mekarsari Village Office, Tambun Selatan District. This research uses qualitative research methods. Data collection techniques in this research are observation, interviews, and also direct documentation at the Tambun Selatan village office. The location of this research is at the Mekarsari Tambun Selatan Village Office. The informants in this research were 2 people. 1 employee as Head of Services and 1 Community member as service recipient. Data analysis in this research has three components, namely data reduction, data presentation, and drawing conclusions. The results of this research indicate that the service that has not been provided from employees to the community has not been maximized. The indicators that are not in accordance with Empathy are lack of communication in tangible services, namely lack of facilities in the service process and reliability, namely lack of friendly employees in the service process.